History as the subject of philosophical studies. On a critical-historical method of Léon Brunschvicg - Ples, Marta (Folia Philosophica, 2007)
A critical-historical method proposed by Léon Brunschvicg is based on the assumption, according to which the subject of analysis should constitute recorded in history acts of human thought. Thus, the history of science is, according to the thinker, the only source of the knowledge in our cognition, whereas an identification of the conditions of capacity and cognition limits constitutes, in accordance with the assumptions of Brunschvicg’s critical idealism, a fundamental task of philosophy. An interpretation of the history of thoughts as an appropriate subject of a philosophical reflection is connected with numerous difficulties deriving from the incongruence of the rational and historical. The attempts the philosophers made to combine these two orders lead inevitably to a reduction of one them. Brunschvicg’s conception is also connected with numerous difficulties, which is reflected in numerous polemic opinions on this philosophical conception, as well as the method worked out on its basis.